(Non)Parallel developmental mechanisms in vertebrate appendage reduction and loss. Issue 22 (22nd October 2021) - Swank, Samantha; Sanger, Thomas J.; Stuart, Yoel E.
Abstract: Appendages have been reduced or lost hundreds of times during vertebrate evolution. This phenotypic convergence may be underlain by shared or different molecular mechanisms in distantly related vertebrate clades. To investigate, we reviewed the developmental and evolutionary literature of appendage reduction and loss in more than a dozen vertebrate genera from fish to mammals. We found that appendage reduction and loss was nearly always driven by modified gene expression as opposed to changes in coding sequences. Moreover, expression of the same genes was repeatedly modified across vertebrate taxa. However, the specific mechanisms by which expression was modified were rarely shared. The multiple routes to appendage reduction and loss suggest that adaptive loss of function phenotypes might arise routinely through changes in expression of key developmental genes. Abstract : Appendages have been independently reduced or lost hundreds of times during vertebrate evolution. Despite that selection seems to routinely favor a reduced appendage, we found that the specific mechanisms to appendage reduction and loss are rarely shared, even when the same genes were involved.